Democracy and racism: from the crisis to the construction of an Anti-Racist Democracy - Vieira, Hector Luis Cordeiro (2024)
The debate on democracy focuses on the model of society formatted from socioeconomic and cultural processes that mirror the various sociopolitical elements that constitute it. In this context, race and racism must be considered essential categories for understanding national societies and modern democracies. The objective of the research is to establish the relationship between racism and democracy, given the premise that, without considering that, it is not possible to build solid democracy, structures that do not articulate the collective demands in an egalitarian way in the decision-making instances of society and the State. It focuses on the institutionalization of racism by whiteness in the judiciary and the proposal for democratic reinvention antiracist.